Critical shoulder angle is an effective radiographic parameter that is associated with rotator cuff tears and osteoarthritis: a systematic review. Issue 2 (7th March 2019) - Kuper, Gabriel; Shanmugaraj, Ajaykumar; Horner, Nolan S; Ekhtiari, Seper; Simunovic, Nicole; Cadet, Edwin R; Ayeni, Olufemi R
Abstract : Importance: The critical shoulder angle (CSA) is a relatively new radiographic parameter correlated with pathologies such as rotator cuff tears and osteoarthritis. Objective: The purpose of this systematic review was to: (1) determine the degree of correlation between the CSA and shoulder pathologies, (2) determine the reliability of measuring CSA between (inter-rater reliability) and within (intrarater reliability) clinicians, (3) assess the accuracy of different imaging modalities used for measuring the CSA and (4) determine the association of CSA with patient outcomes after surgery. Evidence review: The electronic databases MEDLINE, EMBASE and PubMed were searched in March 2018 for relevant studies. The results are presented in a narrative summary. Findings: A total of 26 studies and 4563 patients satisfied the inclusion criteria. The majority of CSAs were measured using radiographs (98.2%) in neutral rotation (72.9%). Significant associations (p<0.05) were found between lower CSAs (<30°) and osteoarthritis, and higher CSAs (>35°) with primary rotator cuff tears and the risk of re-tear following a repair. The CSA has excellent intrarater (intraclass correlation coefficient (ICC) 0.903 to 0.996) and inter-rater reliability (ICC 0.869 to 0.980) when measured with radiographs. High variability in measurements was found when using MRI. The CSA, however, is not a clear, significant independent predictor (p>0.05) of outcomes after the surgical management of shoulder pathologies. Conclusions and relevance: The CSA is an effective radiographic parameter that is associated with rotator cuff tears and osteoarthritis. Lower CSAs (<30°) are associated with osteoarthritis, whereas higher CSAs (>35°) are associated with primary rotator cuff tears and re-tear after arthroscopic repair. Currently, there is a limited predictive value of the CSA in patient-reported outcomes after rotator cuff repair. The CSA is measured with high intrarater and inter-rater reliability for both radiographs and CT scans. Measuring the CSA using radiographs with the arm in the neutral rotation is currently recommended. Future studies are required to further investigate how best use the CSA to guide patient management and its predictive value. Level of evidence: IV.